GAMBARAN PENGETAHUAN MASYARAKAT DALAM PENGOBATAN SENDIRI (SWAMEDIKASI) UNTUK OBAT ANALGESIK - Chusun, Chusun; Lestari, Nanda Sinta (Jurnal Riset Kefarmasian Indonesia, 2020)
Self-medication is an alternative that is taken by the community to increase the affordability of treatment. This study aims to determine the description of Community Knowledge in Self-medication (Self-medication) for analgesics in Sukmajaya Village - Depok City. This research uses descriptive quantitative method. Samples were taken as many as 250 respondents from RW 09 and RW 10. Samples were taken randomly, the data obtained were analyzed univariate and bivariate with SPSS 20. The results showed that from 250 respondents, (90%) conducted self-medication with analgesic drugs, public knowledge. about high self-medication (72%) as well as knowledge of analgesics (58.8%). There is a significant relationship between education and self-medication, namely respondents who have low education have a chance of doing self-medication as well as knowledge of self-medication, namely respondents who have high self-medication knowledge have a chance of 3,193 times to do self-medication. The reason respondents did self-medication was because the disease was considered mild (52.4%). Source of drug information mostly comes from electronic media (88%). The analgesic drug that is widely used is paracetamol (63.6%).